A Facile Catalytic One-Pot Synthesis of Benzimidazole and Benzothiazole Compounds using Amberlite IRA 400-Cl Resin as Green Catalyst - David Amalraj, S.; Harichandran, G.; Bhakiaraj, D.; Amalorpavadoss, A. (Asian Journal of Chemistry, 2022)
A series of pharmaceutically valuable functionalized fused heteroaromatic compounds such as benzimidazoles and benzothiazoles have been synthesized via catalytic cyclocondensation between 1,2-phenylenediamine or 2-aminothiophenol and aryl aldehydes at ambient conditions. The Amberlite IRA400-Cl resin have been proved to be an efficient green catalyst in this protocol. The salient features of this method are the mild condition, easy work-up, an excellent yield of product, green catalyst and reusability of the catalyst.